Implementation of an Embedded In-Clinic Genetic Testing Station to Optimize Germline Testing for Patients with Pancreatic Adenocarcinoma. (20th September 2021) - Walker, Evan J.; Goldberg, Dena; Gordon, Kelly M.; Pedley, Christina; Carnevale, Julia; Cinar, Pelin; Collisson, Eric A.; Tempero, Margaret A.; Ko, Andrew H.; Blanco, Amie M.; Dhawan, Mallika
Abstract : Background: Germline genetic testing is universally recommended for patients with pancreatic cancer, but testing remains infrequent. In May 2018, we implemented a systematic patient intake workflow featuring an in-clinic genetic testing station (GTS) at the University of California San Francisco (UCSF) to expedite genetic counseling and facilitate sample collection. We sought to determine the impact of this innovation on rates of genetic counseling and testing. Methods: Medical records, patient intake records, and genetic test reports were retrospectively reviewed for new patients with pancreatic cancer eligible for germline testing at UCSF from May 2018 to May 2019. Primary outcomes included the rate of offered genetic counseling and confirmed germline testing. Data were compared for periods before and after GTS implementation. Associations between demographic characteristics and testing rates were assessed. Results: Genetic counseling/testing was offered to 209 (94%) of 223 eligible patients, and 158 (71%) completed testing (135 at UCSF, 23 elsewhere). Compared with a traditional referral-based genetic counseling model, confirmed testing increased from 19% to 71%, patient attrition between referral and genetics appointment decreased from 36% to 3%, and rate of pathogenic variant detection increased from 20% to 33%. Patients who were younger, identified as non-Hispanic White, and spoke English as a primary language were more likely to complete testing. Conclusions: Implementation of a systematic patient intake workflow and in-clinic GTS resulted in the highest reported real-world rate of germline testing for patients with pancreatic cancer. Health care disparities were identified and will guide future innovation. This report provides a model for other centers to create a similar testing infrastructure. Implications for Practice: This study demonstrates that a systematic patient intake workflow and associated in-clinic genetic testing station improve delivery of genetic counseling and completion of germline testing for patients with pancreatic cancer. This study achieved, to the authors' knowledge, the highest real-world rate of confirmed genetic testing in this patient population. This article describes this innovation in detail to guide replication at other medical centers and facilitate guideline-concordant care for patients with pancreatic cancer. This infrastructure can also be applied to other cancers for which germline testing is recommended. Abstract : Germline genetic testing is universally recommended for patients with pancreatic cancer, but testing remains infrequent. This article reports a patient intake workflow that was implemented to expedite genetic counseling and facilitate sample collection. The authors describe the impact of this innovation on rates of genetic counseling and testing.